Praying to stop being an atheist - Mawson, T (Springer, 2010)
In this paper, I argue that atheists who think that the issue of God's existence or non-existence is an important one; assign a greater than negligible probability to God's existence; and are not in possession of a plausible argument for scepticism about the truth-directedness of uttering such prayers in their own cases, are under a prima facie obligation to pray to God that He stop them being atheists.